2018
DOI: 10.1017/s0024282917000688
|View full text |Cite
|
Sign up to set email alerts
|

Two new species ofArthoniaceaefrom old-growth European forests,Arthonia thorianaandInoderma sorediatum, and a new genus forSchismatomma niveum

Abstract: Two new species of Arthoniaceae are described from old-growth European forests: Arthonia thoriana from Horner Combe in Great Britain and Inoderma sorediatum from the Białowieża Forest in Poland. Phylogenetic analyses using mtSSU sequences were used to determine the generic affiliation of the two species. Arthonia thoriana is characterized by a non-lichenized white thallus, pallid brown, white pruinose ascomata of 0·12–0·30 mm diam., richly anastomosing paraphysoids and (1–2–)3-septate ascospores of 9–12×3·0–3·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The nomenclature of lichen species followed Fałtynowicz and Kossowska (2016), and for those not included in the previous work, Sérusiaux et al (2010), Czarnota and Guzow-Krzemińska (2018), Ertz et al (2018), Boluda et al (2019). The collected material was deposited in the lichen herbarium of the Jan Kochanowski University in Kielce (KTC) and the University of Gdańsk (UGDA).…”
Section: Methodsmentioning
confidence: 99%
“…The nomenclature of lichen species followed Fałtynowicz and Kossowska (2016), and for those not included in the previous work, Sérusiaux et al (2010), Czarnota and Guzow-Krzemińska (2018), Ertz et al (2018), Boluda et al (2019). The collected material was deposited in the lichen herbarium of the Jan Kochanowski University in Kielce (KTC) and the University of Gdańsk (UGDA).…”
Section: Methodsmentioning
confidence: 99%
“…A targeted fragment of ~0.8 kb of the mitochondrial ribosomal RNA small subunit (mtSSU) was amplified for Granulopyrenis, Loekoesia, Porina, Pyrenula and Squamulea using primers mrSSU1 and mrSSU3R (Zoller et al 1999), and a fragment of ~1 kb of the RPB2 protein-coding gene was amplified for Baidera and Nyungwea using primers fRPB2-7cF and fRPB2-11aR (Liu et al 1999). Amplification reactions were prepared for a 50 µl final volume containing the lichen material as explained in Ertz et al (2018b). The yield of the PCRs was verified by running the products on a 1% agarose gel using ethidium bromide.…”
Section: Molecular Techniquesmentioning
confidence: 99%
“…This order includes five to six families of crustose and fruticose lichens 36 . The conidiomata of the fossil closely resemble those of some Inoderma and Lecanactis species 37,38 . However, the fossil cannot be assigned to any one genus, especially as it has recently been shown that the traditional morphology-based circumscription of taxa within Arthoniales does not correspond with gene-derived phylogenies 36,3941 .…”
Section: Discussionmentioning
confidence: 68%